2008
DOI: 10.1007/s11096-008-9197-4
|View full text |Cite
|
Sign up to set email alerts
|

Medication persistence among patients with asthma/COPD drugs

Abstract: The majority of the patients, and particularly those in the youngest age group used asthma/COPD drugs only sporadically. This may indicate undermedication which is likely to have a negative impact on patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 24 publications
3
37
0
1
Order By: Relevance
“…A number of studies have explored the prescribing of antiasthmatic drugs in Sweden [8][9][10][11]. Some studies have focused on equity, safety, and regional variation [12][13][14], but most are old studies that included only small populations, did not focus on asthma, dealt with children only, and/or were concerned with acute rather than chronic care.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have explored the prescribing of antiasthmatic drugs in Sweden [8][9][10][11]. Some studies have focused on equity, safety, and regional variation [12][13][14], but most are old studies that included only small populations, did not focus on asthma, dealt with children only, and/or were concerned with acute rather than chronic care.…”
Section: Introductionmentioning
confidence: 99%
“…The cost of nonadherence by patients with chronic diseases is estimated to be $300 billion/y in the United States. 12 According to previous research, the adherence rate of subjects with COPD is Ͼ 50% [13][14][15][16][17][18] as opposed to 30 -70% in subjects with asthma. 19 Patient adherence tends to be lower in the evening and declines over time.…”
Section: Problems With Patient Education and Adherence To Aerosol Thementioning
confidence: 99%
“…19 Patient adherence tends to be lower in the evening and declines over time. 14,[20][21][22] Jónasson et al 23 determined the mean adherence rates of 122 children 7 to 16 y of age over a 27-month period using an electronic device monitor. Their findings showed that the mean adherence rate at 3 months was 76.7% compared with 44% by end of the study.…”
Section: Problems With Patient Education and Adherence To Aerosol Thementioning
confidence: 99%
See 1 more Smart Citation
“…Less than perfect adherence to ICS appears to account for the majority of asthma-related hospitalizations (4,5). The reported adherence rate of COPD and asthma patients is about 50% and 30-70%, respectively (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%